IMAM AL-TIRMIDHI AND HIS CONTRIBUTION TO ISLAMIC SCHOLARSHIP: A CRITICAL ANALYTICAL ARTICLE WITH HISTORICAL FACTS AND SCHOLARLY IMPACT ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
This article examines the life, scholarly contributions, and intellectual legacy of Imam al-Tirmidhi, one of the most prominent figures in Islamic tradition. Although not a medical scholar, his rigorous methodological framework in Hadith sciences contributed indirectly to the development of evidence-based thinking, which later influenced various scientific disciplines, including medicine in the Islamic Golden Age. Using historical data, classical sources, and modern academic interpretations, this paper highlights his methodological innovations, statistical contributions to Hadith classification, and his broader impact on epistemology in Islamic civilization.